Dignity through Discourse : Poverty and the Culture of Deliberation in Indian Village Democracies - Rao, Vijayendra (2012)
Employing a view of culture as a communicative phenomenon involving discursive engagement, the authors argue that the struggle to break free of poverty is as much a cultural process as it is political and economic. The authors analyze public meetings in Indian village democracies, gram sabhas, where villagers are constitutionally empowered to make decisions regarding budgetary allocations for village development and beneficiary selection for antipoverty programs. They examine 290 transcripts of gram sabhas from South India, looking at how they create a culture of civic/political engagement and how the definition of poverty is understood within them. They highlight how gram sabhas impart discursive skills and civic agency and illustrate how the poor deploy these skills in a resource-scarce and socially stratified environment. The intersection of poverty, culture, and deliberative democracy sheds light on cultural processes that can be influenced by public action in a manner that helps improve the voice and agency of the poor.